2014
DOI: 10.1213/ane.0b013e3182a8fab5
|View full text |Cite
|
Sign up to set email alerts
|

Academic Productivity of Directors of ACGME-Accredited Residency Programs in Surgery and Anesthesiology

Abstract: Background Scholarly activity is expected of program directors of the Accreditation Council for Graduate Medical Education (ACGME)-accredited residency training programs. Anesthesiology residency programs are cited more often than surgical programs for deficiencies in academic productivity. We hypothesized that this may in part reflect differences in scholarly activity between program directors of anesthesiology and surgical trainings programs. To test the hypothesis, we examined the career track record of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools.…”
Section: Resultsmentioning
confidence: 99%
“…The h-index has been extensively studied in medicine and dentistry, with most studies demonstrating a strong correlation between the h-index and academic rank. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools. Nonetheless, the h-index remains the most extensively studied tool for assessing academic productivity.…”
Section: Resultsmentioning
confidence: 99%
“…5 Thus, residents interested in incorporating research or a fellowship into their career may have a competitive advantage in hiring processes at academic institutions. 5,24,25 The four most popular anesthesia subspecialties were regional anesthesia, intensive care, cardiac anesthesia, and acute or chronic pain. The popularity of regional anesthesia may be to increase skill in performing regional blocks, as many U.S. anesthesia residents finish their residency training and are still not confident in performing certain regional block techniques.…”
Section: Future Practice Locationmentioning
confidence: 99%
“…Among all plastic surgeons, an h‐index of 7 (range 0–62) has been reported, while a study of hand surgeons revealed a comparable mean h‐index of 10.2 (Gast et al, ; Lopez et al, ). Studies of other surgical fields have also yielded similar results: orthopedic surgeons, h‐index 11 (IQR 15); hepatic surgeons, h‐index 6 (IQR 10); and general surgeons, h‐index 11 (IQR 15) (Cucchetti et al, ; Culley et al, ; Stavrakis et al, ).…”
Section: Discussionmentioning
confidence: 75%